Model Pembelajaran Klasikal Dalam Pendidikan Anak Usia Dini - Ratnawati, Ratnawati (Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to describe the classical learning model in Early Childhood Education. The research method used is library research method. The data collection method used is the documentation method. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent misinformation in data analysis, inter-library checks and re-reading of the literature as well as attention to the supervisor's comments are carried out. The results of this study are 1) The classical learning model is a learning pattern where at the same time, all children are carried out in the same class. This learning model is the earliest model used in Early Childhood Education. classical learning in carrying out a teaching and learning process, the teacher should do it using various learning approaches. Teaching activities carried out by teachers with a certain approach will be meaningful, if the material given to students can be understood by most students or all students. 2) Implementation of the classical learning model in Early Childhood Education in a fun way, for example starting with praying, attending, singing according to the theme, clapping, discussing and asking questions about themes and sub-themes or experiences experienced by children and using various media